2022
DOI: 10.3390/medsci10040053
|View full text |Cite
|
Sign up to set email alerts
|

Time to Load Up–Resistance Training Can Improve the Health of Women with Polycystic Ovary Syndrome (PCOS): A Scoping Review

Abstract: Background: Guidelines for the management of polycystic ovary syndrome (PCOS) focus on lifestyle changes, incorporating exercise. Whilst evidence suggests that aerobic exercise may be beneficial, less is known about the effectiveness of resistance training (RT), which may be more feasible for those that have low fitness levels and/or are unable to tolerate/participate in aerobic exercise. Objectives: To identify the available evidence on RT in women with PCOS and to summarise findings in the context of a scopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Regarding the latter, a systematic review and meta-analysis by our group [22] showed a statistically beneficial change from baseline for insulin sensitivity, lipid profile, waist circumference, and cardiorespiratory fitness (VO 2 max/peak) in women with PCOS completing exercise interventions, when compared to those in a control group. Similarly, a scoping review revealed potentially beneficial effects of resistance training programmes on a range of pertinent outcomes (e.g., glycaemic control, body composition, and androgens) in women with PCOS [23]. However, the findings of our systematic reviews also highlighted that research regarding exercise/PA interventions in women with PCOS remains limited and that well-designed studies are still needed in this field.…”
Section: Introductionmentioning
confidence: 70%
“…Regarding the latter, a systematic review and meta-analysis by our group [22] showed a statistically beneficial change from baseline for insulin sensitivity, lipid profile, waist circumference, and cardiorespiratory fitness (VO 2 max/peak) in women with PCOS completing exercise interventions, when compared to those in a control group. Similarly, a scoping review revealed potentially beneficial effects of resistance training programmes on a range of pertinent outcomes (e.g., glycaemic control, body composition, and androgens) in women with PCOS [23]. However, the findings of our systematic reviews also highlighted that research regarding exercise/PA interventions in women with PCOS remains limited and that well-designed studies are still needed in this field.…”
Section: Introductionmentioning
confidence: 70%
“…In a study by Kite et al, 98 where they evaluated part of resistance training in women who could not tolerate aerobic exercises in contrast to healthier ones who could perform them .They concluded that statistical alterations were documented to be associated with metabolic(like glycemia along with fat free mass ) as well as hormonal (like T, in addition to sex hormone binding globulin(SHBG),profiles .As per their conclusions absence of enough studies this arena, they illustrated that the degree of alterations was minimal and although documented statistically significant for numerous results ,the revealed results of alterations along with quality of proof is queried. Thus stressed on how good fashioned / documented as well as adequately powered trials are required.…”
Section: Part Of Resistance Trainingmentioning
confidence: 97%